Proses Alih Teknologi E-Administrasi Pilkades Cianjur 2025-2026 Meningkatkan Profesionalisme dan Akuntabilitas - Mulyadi, Dedi; Utami, Tanti Kirana; Kuswandi, Kuswandi; Nur, Hilman; Mulyana, Aji; Azahra, Anisa Amalia; Ramadani, Azzahra Salsabila; Aulia, Salsabila Hadi; Kusworo, Fuji Raihan Azhari; Kintara, Ikhsan (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
Village Head Elections are a manifestation of village democracy in order to determine qualified village leadership. In Law Number 6 of 2014 concerning Villages, Article 31 Paragraphs (1) and (2) states that Village Head Elections are held simultaneously in all Regency / City areas. The rapid development of technology in the era of the industrial revolution 4.0 has affected many things, one of which is in the process of simultaneous village head elections, the government can utilize technology by creating an E-Administration system policy in the registration process. This E-Administration system aims to increase professionalism and accountability both to the community and stakeholders. The method of implementation in this research is through forum group discussions involving the research team, supporting team, surveyor team, and several stakeholders. The results of this study are that after several discussions between the research team, supporting team, surveyor team, and several stakeholders, all parties agreed and equalized perceptions regarding the technical implementation of the 2025-2026 simultaneous village head elections in Cianjur Regency.